Toward thin GaSb Buffer Layers Grown on On‐Axis (001) Silicon by Molecular Beam Epitaxy - A. Gilbert; M. Ramonda; G. Patriarche; E. Tournié; J.‐B. Rodriguez (Advanced Physics Research)
Abstract The monolithic integration of III‐Vs on Silicon (Si) is of great interest for the development of active photonic integrated circuits (PICs). The main challenge is to achieve a high‐quality epitaxy of the III‐V on the Si substrate, as the differences between the materials are responsible for the formation of crystal defects, in particular threading dislocations (TDs) and antiphase domains (APDs) delineated by antiphase boundaries (APBs), which degrade the device's performance. A new technique is demonstrated to achieve thin APBs‐free GaSb buffer layers grown on Si substrates. The original idea presented in this paper is to introduce a GaAs layer into the buffer to promote faster burial of APDs. Two strategies are compared; the first one involves the complete APDs burying in GaAs before growing GaSb, while the second one uses a thin GaAs layer before burying the APDs in the GaSb layer. APB‐free buffer layers as thin as 215/400 nm have been obtained using the first method, which represents a factor of 2/4 thickness reduction compared to the previous results for both 0.5° and 0.2° miscut angles.